Sistem Pakar Menggunakan Metode Forward Chaining Untuk Identifikasi Penerimaan Beasiswa di Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi - Tri, Tri Agusti Farma; Yuhandri; Widi Nurcahyo, Gunadi (RJOCS (Riau Journal of Computer Science), 2023)
Scholarships are one way of providing tuition fees for students who are still actively participating in lectures at tertiary institutions. The existence of scholarships can help students to finance educational needs, in accordance with the provisions of article 4 (paragraph 1) of the PPh/2000 Law. This study aims to build a system of indicators for determining scholarship acceptance appropriately. Expert System is the ability of computers to convert human knowledge into computers so that they can help solve problems that can only be solved by experts. The scholarship acceptance identification expert system is a system that adopts the knowledge of education experts in determining scholarship acceptance for students at university based on scholarships that have been set at the university. The purpose of this Expert System is to prove that the Forward Chaining method can be implemented in making this Expert System and provide benefits to facilitate campus bureaucrats in determining which students are eligible to receive scholarships. The data used in this study were 10 student data, in the form of scholarship requirements and student diagnostic data by the head of the academic division. The data is processed using the Forward Chaining Inference method in the form of an application with the PHP programming language. The results of this study were 30 student data running well on the system used. An expert system with the Forward Chaining method is suitable and can be used to determine scholarship acceptance.